Fresh, Mechanical and Absorption Characteristics of Self-Consolidating Concretes Including Low Volume Waste PET Granules - Kasım Mermerdaş; Dia Eddin Nassani; Mehmet Sakin (Civil Engineering Journal, 2017)
This study evaluates the effect of waste polyethylene terephthalate (PET) granules on the fresh, mechanical and absorption characteristics of self-consolidating concretes (SCCs). Fine aggregates were replaced with different percentages (from 0% to 8%) of PET granules obtained by crushing waste PET bottles. The fresh properties of SCC containing PET granules were determined using slump flow and V-funnel flow time tests. Mechanical properties (compressive strength and splitting tensile strength tests) and absorption properties (sorptivity and water absorption tests) were evaluated. The results indicated that utilization of waste PET granules in production of SCC could be an effective way for recycling purpose. The maximum amount of PET replacement should be limited to 5%. Exceeding 5% of PET content may result in an increase of V-funnel flow time to overpass the limiting value, decrease in compressive strength, reduction in sorptivity and increase in the water absorption. The production of high performance SCC containing 5% PET granules satisfies all the requirements for SCC with satisfactory outputs.